2010
DOI: 10.1121/1.3385381
|View full text |Cite
|
Sign up to set email alerts
|

Testing the temporal robustness of an automatic aural classifier.

Abstract: Military sonar systems must detect and classify submarine threats at ranges safely outside their circle of attack. However, in littoral environments, echoes from geological features (clutter) are frequently mistaken for targets of interest, resulting in degraded performance. Perceptual signal features similar to those employed in the human auditory system can be used to automatically discriminate between target and clutter echoes, thereby improving sonar performance. [J. Acoust. Soc. Am. 122, 1502–1517 (2007)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Also of note is that the elements above the main diagonal are darker (i.e., represent better performance) than those below the main diagonal. A similar pattern was noted in the SNR-dependence investigation of Murphy and Hines [7], suggesting that SNR may, at least in part, be driving the decrease in classifier performance. Mouy et al [14] also noted that false negative rates increased as SNR decreased.…”
Section: Figure 3: Aural Classifier Performance Matrices Generated Frsupporting
confidence: 71%
See 1 more Smart Citation
“…Also of note is that the elements above the main diagonal are darker (i.e., represent better performance) than those below the main diagonal. A similar pattern was noted in the SNR-dependence investigation of Murphy and Hines [7], suggesting that SNR may, at least in part, be driving the decrease in classifier performance. Mouy et al [14] also noted that false negative rates increased as SNR decreased.…”
Section: Figure 3: Aural Classifier Performance Matrices Generated Frsupporting
confidence: 71%
“…Alternatively, it may be found that many of the perceptual features are environment-sensitive and therefore it is unreasonable to exclude all of them. In this case, a strategy may instead be developed to generate training sets for the classifier that take propagation-related signal distortion into account; this could be done either by acoustically distorting the training data by propagating them through a modeled environment or by including vocalizations in the training set that came from a variety of propagation ranges as done in [7,8].…”
mentioning
confidence: 99%
“…To In general, the performance matrices generated using data from each recording unit displayed similar trends -the example results in Hines [79], further suggesting that SNR, at least in part, was responsible for driving the observed decrease in classifier performance. Mouy et al [23] also noted that false negative rates increased as SNR decreased.…”
Section: Training Set Selectionmentioning
confidence: 63%
“…In this section, we consider if high SNR signals recorded close to the sound source are the best for training the aural classifier. Murphy and Hines [79] concluded in their research with active sonar echoes that given two or more datasets with different SNR, the aural classifier performed better across multiple SNR regimes when the classifier was trained on a low SNR dataset. They ascribed this finding to the perceptual feature subset selected based on the signals contained in the training set -features selected from a high SNR training set did not perform well at low SNRs because the signal characteristics these features depended on became lost in the noise as SNR decreased, whereas features that were selected from the low SNR signals relied on signal characteristics that were still present in the higher SNR signals.…”
Section: Training Set Selectionmentioning
confidence: 99%
“…Propagation effects on the performance of the aural classifier may be analogous to the dependence of the aural classifier's performance on the Signal to Noise Ratio (SNR) levels of active sonar echoes. Work done by Murphy and Hines [7] demonstrated that higher performance was achieved when the classifier was trained with echoes of a similar SNR to the SNR of the data in a test set. It was also found that if echoes in the test set had a range of SNR values, the best performance was achieved by training the classifier with echoes that also encompassed a wide range of SNR values.…”
Section: Resultsmentioning
confidence: 99%